Konstruksi Nasionalisme Religius dalam Lirik Lagu Yā Lal Waṭan: Analisis Pragmatik Tindak Ilokusi - Zainurrakhmah; Arbi Mulya Sirait (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2026)
This study examines the pragmatic construction of religious nationalism in the lyrics of the song Yā Lal Waṭan through speech act theory. Widely associated with the tradition of Nahdlatul Ulama, the song functions not only as artistic expression but also as a performative medium that conveys nationalist commitment through Islamic discourse. This research aims to analyze how illocutionary functions in the lyrics contribute to the construction of a religiously grounded nationalist identity. The study employs pragmatic analysis based on speech act theory proposed by J. L. Austin (1962) and John R. Searle (1969), examining selected lyric units within their linguistic and socio-cultural contexts. The findings show that the lyrics integrate several illocutionary functions—expressive, assertive, directive, and commissive—forming a layered rhetorical structure that promotes religious nationalism. Expressive acts evoke emotional attachment and devotion to the homeland, assertive acts establish the ideological linkage between nationalism and Islamic values, directive acts encourage collective action in defending the nation, and commissive acts imply a shared commitment to safeguarding national unity. These findings demonstrate that the lyrics function not merely as aesthetic discourse but as a performative linguistic mechanism that reinforces collective identity and nationalist commitment within a religious framework.